Engaging the Public with and Preserving the History of Texas’s First Public Historically Black University - Robinson, Marco; Earles, Phyllis (KULA, 2018)
The silences and erasures surrounding the histories of historically black colleges and universities (HBCUs) in many instances are caused by limited technology, lack of financial resources, and, most importantly, institutional priorities. Many aspects of HBCUs’ histories, particularly in the state of Texas, have been relegated to historical voids or are becoming endangered knowledge. These are the issues that jeopardize the long and rich history of Prairie View A&M University (PVAMU), Texas’s first public supported historically black university, which dates back to the post-Reconstruction and Jim Crow eras of American history. Emancipated blacks in Texas sought all avenues available to them to obtain an education, including establishing churches and schools. Freed people’s efforts culminated in the creation of Alta Vista School for Colored Youth, which subsequently became PVAMU following several name changes. During the Jim Crow era, PVAMU served as the administrative home base for black education in the state of Texas, offered agricultural extension services to black farmers, and served as the central facility for black grade school athletics and extracurricular activities. Due to lack of personnel and resources, all of the archival collections that document this history are unprocessed and unavailable to the public. This article considers the collaborative efforts of the history faculty and the Special Collections and Archives (SCAD) staff at PVAMU to bring light to this important history through preservation projects, public programming and student engagement activities. Additionally, the article uses endangered archival materials from PVAMU’s Special Collections to explore the history of this important institution of higher education.